Self-transformation of ultra-small gold nanoclusters to gold nanocrystals toward boosted photoreduction catalysis. Issue 71 (19th August 2019) - Huang, Ming-Hui; Li, Yu-Bing; Li, Tao; Dai, Xiao-Cheng; Hou, Shuo; He, Yunhui; Xiao, Guangcan; Xiao, Fang-Xing
Abstract : Self-transformation of Au clusters to Au nanocrystals (NCs) was achieved via thermal reduction and Au NCs integrated at the interface of CdSe QDs and graphene boost interfacial charge transfer efficiency. Abstract : Glutathione-protected Au x nanoclusters uniformly and intimately embedded at the interface of CdSe QDs and graphene were in situ self-transformed to Au nanocrystals (NCs) via a facile thermal reduction strategy. The inlaid Au NPs substantially accelerate the interfacial directional charge transfer toward multifarious photoreduction catalysis under visible light irradiation.